Zygapophysial Joint Pain in Post Lumbar Surgery Syndrome. The Efficacy of Medial Branch Blocks and Radiofrequency Neurotomy. Issue 3 (13th December 2012) - Klessinger, Stephan
Abstract Objective To investigate the prevalence of zygapophysial joint pain in patients after disc surgery, and to determine the effectiveness of radiofrequency neurotomy for its treatment. Design Retrospective practice audit. Setting Review of charts of all patients who underwent lumbar disc surgery during a time period of 2 years. Interventions Patients with persistent back pain after surgery were tested with repeated medial branch blocks. Those patients who consistently report at least 80% pain relief underwent radiofrequency neurotomy. A successful outcome was defined as at least 50% pain reduction enduring for 6 months. Results In a population of 479 patients who underwent microsurgical lumbar disc operations, persistent axial back pain occurred in 120, of whom 34 had positive responses to diagnostic blocks and were treated with radiofrequency neurotomy. Twenty patients (58.8%) achieved at least 50% reduction in pain for a minimum of 6 months. Conclusions The prevalence of zygapophysial joint pain appears to be 7% in patients with failed back surgery syndrome. Patients with this condition can be treated with a radiofrequency neurotomy with a success rate of 58.8%.